2017
DOI: 10.1037/prj0000278
|View full text |Cite
|
Sign up to set email alerts
|

Development and usability testing of a web-based decision support for users and health professionals in psychiatric services.

Abstract: This web-based decision aid has the potential to strengthen service users' experience of self-efficacy and control as well as provide staff access to user knowledge and preferences. Studies employing participatory models focusing on usability have potential to significantly contribute to the development and implementation of tools that reflect user perspectives. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 41 publications
0
32
0
1
Order By: Relevance
“…The DST features separate, overlapping, web-based interfaces for user and provider, with full transparency between them. The development process and usability evaluation of the DST has been described in greater detail elsewhere (Grim et al, 2017). The purpose of using the DST is to increase user participation influencing the care planning process, as well as offering staff access to the user’s perceptions of their own needs, knowledge which can facilitate the decision-making process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DST features separate, overlapping, web-based interfaces for user and provider, with full transparency between them. The development process and usability evaluation of the DST has been described in greater detail elsewhere (Grim et al, 2017). The purpose of using the DST is to increase user participation influencing the care planning process, as well as offering staff access to the user’s perceptions of their own needs, knowledge which can facilitate the decision-making process.…”
Section: Methodsmentioning
confidence: 99%
“…In the research project, researchers, users, staff and service designers have worked together, a partnership which has generated knowledge regarding needs for support that can enable users to participate in their care (Grim, Rosenberg, Svedberg, & Schön, 2016) validated instruments for measuring SDM (Rosenberg, Svedberg, & Schön, 2015; Schön, Svedberg, & Rosenberg, 2015), as well as contributing to the development and validation of a digital interactive decision support tool, DST , for users in psychiatric care (Grim, Rosenberg, Svedberg, & Schön, 2017). The DST is based on the theoretical framework of SDM (Elwyn et al, 2012) and was adapted to the specific needs and preferences of users with mental health problems in a Swedish context (Grim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The data for this study are derived from the qualitative phases of a multi-phase project performed between 2014 and 2016. The aim of the project was to develop a supportive structure for SDM in the form of a decision support tool (DST) and supporting the implementation of SDM in the context of the Swedish mental healthcare system [16][17][18]. During the development and implementation of SDM, it became evident that the possibilities for user knowledge to be expressed and validated in the kind of joint deliberation that SDM requires were associated with several difficulties.…”
Section: Background Of the Current Studymentioning
confidence: 99%
“…Prior to implementing the DA for clinical decisions, it must be tested among patients making hypothetical decisions. We targeted a convenience sample of fifteen patients, reflecting an appropriate sample size for usability studies [35][36][37], as 80% of usability issues can be identified through 5-8 participants [28].…”
Section: Participants and Samplingmentioning
confidence: 99%